THE INFLUENCE OF ETHICAL SALES BEHAVIOR, BRAND EQUITY, AND CUSTOMER EXPERIENCE ON KETJE COFFEE CUSTOMER LOYALTY IN BANDAR LAMPUNG - Nia Aprilia; Tri Lestira Putri Warganegara (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The objective of this study is to examine the influence of ethical sales behavior, brand equity, and customer experience on customer loyalty at Ketje Coffee in Bandar Lampung. The research population consists of customers of Ketje Coffee in Bandar Lampung, with a sample size of 100 customers. The analysis method employed in this study is multiple linear regression analysis. The research findings indicate that ethical sales behavior, brand equity, and customer experience all have a positive and significant impact on customer loyalty. This implies that ethical sales behavior, brand equity, and customer experience play a crucial role in shaping customer loyalty. The results of this research can assist Ketje Coffee in enhancing ethical sales behavior, strengthening brand equity, and improving customer experience, thereby increasing the company's competitiveness and fostering better customer loyalty. In the current era of heightened business competition, this study provides a platform for Ketje Coffee to enhance customer loyalty and encourage customers to choose Ketje Coffee for their consumption needs.